Impact of COVID-19 on Children and Young Adults With Type 2 Diabetes: A Narrative Review With Emphasis on the Potential of Intermittent Fasting as a Preventive Strategy - Elmajnoun, Hala K.; Faris, MoezAlIslam E.; Uday, Suma; Gorman, Shaun; Greening, James E.; Haris, Parvez I.; Abu-Median, Abu-Bakr (Frontiers in Nutrition, 2021)
Background: The world is struggling to control the COVID-19 pandemic. Most children and adolescents are either asymptomatic or have mild symptoms, with generally good prognosis. It is not well known whether children and young adults with type 2 diabetes are at risk of getting a severe infection of COVID-19, as reported among adults with diabetes. Many children with type 2 diabetes have been performing dawn to dusk fasting during the month of Ramadan, before and during the COVID-19 pandemic, and the impact of this on their health has not been well investigated. Previous studies with adults suggested that intermittent fasting may be beneficial, including reversal of type 2 diabetes and prevention of COVID-19 infection. Objective: The primary aim of this review is to summarise the impacts of the COVID-19 pandemic on children and young adults with type 2 diabetes, and to identify the knowledge gaps in the literature. Also explores the importance of intermittent fasting in reversing the pathogenesis of diabetes. Methods: Several databases, including Google Scholar, Research Gate, PubMed, MEDLINE (EBSCO), and Web of Science were examined. The most common search terms used were “COVID-19 AND Children”, “SARS-CoV-2 AND/OR Children”, “COVID-19 AND Diabetes” “COVID-19 Epidemiology”, “COVID-19 AND Ramadan fasting”, “COVID-19 and Intermittent fasting”. All the resources used are either peer-reviewed articles/reports and/or official websites. Results: It has been found that the incidence of COVID-19 among children with type 2 diabetes seems to be not much different from children without diabetes. Several studies have reported that prevention programmes such as intermittent fasting are effective to protect these groups of patients from developing any complications. Observing Ramadan fasting could be beneficial for some children with established diabetes and people at risk. Conclusion: Children and young adults with type 2 diabetes are not at risk of severe COVID-19 infection as the case in adults with diabetes. More research is needed to identify the impact of COVID-19 and to investigate the efficacy and safety of intermittent fasting programmes among these age groups. It may have a great impact in minimising the incidence of diabetes among these age groups during the current pandemic.